ANALISIS HIDROLOGI KAWASAN DAS BLONGKENG PROPINSI JAWA TENGAH TAHUN 1993 - 2000 - Budianta, Aziz (MEKTEK, 2005)
Blongkeng watershed area is a sub watershed of Progo, located in Magelang District, Center Java Province. Blongkeng watershed is potential catchment area and it contributes on availability of water surface as well as ground water, either locally and regionally. In accordance with Government Act No. 47/1997 which covers National Planning on Regional Space Arrangement, the middle slope to the up-zone of the watershed has been classified as a conservation region especially on water and soil reserve. This study was conducted so as to determine of hydrology characteristics and watershed critical evaluation. Analytical study covered trend analysis and statistical analysis. The results showed that trend of increasing either maximum and maximum-minimum ratio of stream flow, or trend of declining annually average and minimum stream flow. The evaluation of watershed condition with run-off coefficient (C) analysis showed that the watershed was still normal